2022
DOI: 10.1111/socf.12827
|View full text |Cite
|
Sign up to set email alerts
|

Fight‐or‐Flight for America: The Affective Conditioning of Christian Nationalist Ideological Views During the Transition to Adulthood1,2

Abstract: Christian nationalism has gained attention both inside and outside of academia for its powerful influence on sociopolitical attitudes, voting behaviors, and political mobilization. However, limited work has examined how Christian nationalist views develop, the mechanisms by which they relate to sociopolitical attitudes, or potential varieties of Christian nationalism. Building on recent culture and cognition scholarship, this article synthesizes insights from affective neuroscience to conceptualize the fundame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Some sociologists have argued that communities and classes of people can develop emotional biographies (Turner 2010), meaning that emotions are not simply randomly distributed, but like any resource can cluster and cohere in time and space. For instance, research on Christian Nationalists found excessively high exposure to stimuli and, subsequently predispositions to, feeling fear and/or rage when perceiving environmental crises (Rotolo 2022). Consequently, their response to real or imagined crises evoked these affectual responses as though they were innate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some sociologists have argued that communities and classes of people can develop emotional biographies (Turner 2010), meaning that emotions are not simply randomly distributed, but like any resource can cluster and cohere in time and space. For instance, research on Christian Nationalists found excessively high exposure to stimuli and, subsequently predispositions to, feeling fear and/or rage when perceiving environmental crises (Rotolo 2022). Consequently, their response to real or imagined crises evoked these affectual responses as though they were innate.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this social pain borne of rejection and exclusion motivates individuals and, in some cases, collectives to develop defensive strategies designed to protect ego, dignity, and respect (Abrutyn 2023); unfortunately, defensive strategies very often are (or invite pathology that is) harmful to the self and sometimes others (Summers‐Effler 2004). Thus, while beliefs may act as Weber's proverbial “switchman” in determining the course of action a given individual or set of individuals experiencing pain are likely to take, it is the underlying affective neurophysiological response (Kringelbach and Berridge 2016), innate yet conditioned by the environment (Rotolo 2022), that helps explain why some places condition people to respond to similar crises in exceedingly different ways.…”
Section: Modifying Cavan's Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…providing a theoretical explanation for how religious symbols or stimuli external to persons may be drawn on or "used" even by those who are not themselves religiously devout or theologically knowledgeable (Delehanty, Edgell, and Stewart 2019;Rotolo 2022). Such a toolkit could be widespread without being deeply held.…”
Section: Theoretical Gaps In Qcn Literaturementioning
confidence: 99%